PENERAPAN MEDIA GAMBAR UNTUK MENINGKATKAN KETERAMPILAN PEMAHAMAN MEMBACA SISWA KELAS IV UPT SD NEGERI 13 PELANGAI KECIL - Diana, Sepnia; Marta, Eni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Visual media is believed to help students understand reading better because it presents abstract concepts in concrete visual forms. This media also increases motivation, engagement, and active interaction between teachers and students. This research is motivated by the low reading comprehension skills of fourth-grade students at UPT SD Negeri 13 Pelangai Kecil. The purpose of this research is to describe the application and effectiveness of visual media in improving these skills. Classroom Action Research (CAR) using the Kemmis & McTaggart model was conducted in three cycles with nine students as subjects. Data were collected through tests, observations, and documentation, then analyzed quantitatively and qualitatively. The results showed that visual media increased teacher and student activity as well as learning outcomes. The average student score increased from 65.5 (Cycle I) to 72.2 (Cycle II) and reached 91.1 (Cycle III). Classical completion increased from 44.4% (Cycle I) to 55.6% (Cycle II) and 88.9% (Cycle III). The study concluded that image media effectively improved students' reading comprehension skills.